Gamma Radiation (137Cs) for the Treatment Against Resistant Fungi in Two Brazilian Libraries - da Costa, Antonio Carlos Augusto; Arbach, Mayara Nascimento; Melo Ferreira, Ana Cristina de; Lutterbach, Márcia Teresa Soares; Oliveira, Ana Lucia Chaves de (International Journal of Advanced Engineering Research and Science, 2022)
The present work showed that a wide diversity of fungi was found in the environment where the Collection Academia Brasileira de Ciências is stored, in the Henrique Morize Library, being this diversity quite common in spaces storing this kind of cellulosic material. Fungal genera such as Aspergillus, Cladosporium, Rhizopus and Trichoderma were identified through modern Molecular Biology techniques. The presence of these fungal genera is probably associated to climatization and humidity control, which prevent the occurrence of a wider diversity of microbes. However, two fungal genera, Trichoderma and Rhizopus, resisted 137Cs irradiation doses with up to 19 kGy, considered high for the elimination of fungi. On the other hand, in the National Library, particularly in some sectors, an even higher diversity of fungal species/genera was observed, a fact that seems to be compatible with the size of the library, with a much higher circulation of people. This higher microbial diversity indicated the occurrence of fungal species absolutely uncommon for in libraries and archives, such as: Diaphorte, Trametes, Arxotrichum, Grammothele, Pessiophora, Phebia and Talaromyces. Just successive samplings in the same areas will allow a confirmation if these fungal genera are permanent of occasional, due to some oscillation in the operation of circulation systems or a possible transport of these species from the outside to the library, which allows those species to remain latent in relation to growth. All microbial samples from the National Library, survived irradiation up to 16kGy.